(untitled) (Journal of Parents and Teachers, 2014)
Bulimia is an eating disorder that, in most cases, has a psychological origin because it is an uncontrollable fear of getting fat. Generating excessive concern about body weight and physical appearance; in this disorder the person tends to have repeated episodes of excessive intake followed by provocation of vomiting, use of laxatives, etc. At present, there is a cult of aesthetic perfection of physical forms and extreme thinness. As a result, it is essential to address this issue from the family, school and public-private organisations. In the following article, the symptoms presented by people with bulimia and how to detect them, the lines of prevention within the family and the school, etc. are explained.